Islamic Economics and Finance: Trend Topics and Thematic Evolution - As-Salafiyah, Aisyah; Radwan, Maha (SMART Insight, 2023)
This study aims to determine the development and trend map of research on the theme of Islamic Economic and finance published by reputable journals. The data used in this study are 2498 public indexed research on the theme of Islamic Economic and finance in the period 1976 to 2021. The map of research development in the field of Islamic Economic and finance is obtained through an export process which will be processed and analyzed using the R Biblioshiny application program. This study shows the results that the number of publications on the development of Islamic Economic and finance research has increased significantly. In addition, the results show that the journal that publishes the most and has the greatest impact on Islamic Economic and finance research is the Journal of Islamic and Middle Eastern Finance and Management. The author with the longest publication track record is Wilson R while the author with the highest quantity of publications is Hassan MK. The educational affiliation that has the most and relevant publications is International Islamic University Malaysi. The results also show that the most used topic keywords are Islamic, Finance, Banking, and Financial.